Structured Consensus‐Building to Improve Pressure Injury Prevention Interventions in Acute Medical‐Surgical Hospital Settings: A Nominal Group Technique Study - Jake McMahon; Ching Shan Wan; Nicola Straiton; Louisa Lam; Jane Rodgers; Jenny Sim (Journal of Clinical Nursing, 2026)
ABSTRACT Aim To gain consensus and prioritise barriers to effective pressure injury prevention for at‐risk patients and to collaboratively generate, discuss and recommend intervention strategies that could address these prioritised barriers in the acute medical‐surgical hospital context. Design Nominal Group Technique. Methods Participants involved in pressure injury prevention across acute medical‐surgical services in a tertiary hospital in Australia were purposively sampled. Pre‐reading materials informed the discussion on barriers to prevention. Participants ranked 11 barriers that were collaboratively developed and identified practical context‐specific solutions. Data were analysed using inductive content analysis. Results Nine multidisciplinary participants prioritised three final barriers to effective pressure injury prevention: inadequate skin assessment and monitoring, competing priorities and workflow pressures and insufficient education and inconsistent knowledge. Proposed solutions focused on developing concise, accessible decision support tools such as quick reference flowcharts to enhance confidence, consistency and timeliness of appropriate pressure injury prevention practices. Conclusions The Nominal Group Technique enabled consensus‐building, guided the development of actionable priorities and informed targeted intervention strategies to address key barriers in acute care nursing practice. Implications for the Profession and/or Patient Care Findings from this study offer nurse leaders and researchers practical insights to co‐create an intervention that drives evidence‐based pressure injury prevention practice change in acute medical‐surgical settings. Adoption of these targeted approaches may enhance hospital patient safety through pressure injury prevention implementation. Reporting Method Reporting guideline for PRIority Setting on health research (REPRISE). Patient or Public Contribution No patient or public contribution.